2023
DOI: 10.1029/2022ef002765
|View full text |Cite
|
Sign up to set email alerts
|

Carbonates in the Critical Zone

Abstract: Earth's Critical Zone (CZ), the near‐surface layer where rock is weathered and landscapes co‐evolve with life, is profoundly influenced by the type of underlying bedrock. Previous studies employing the CZ framework have focused primarily on landscapes dominated by silicate rocks. However, carbonate rocks crop out on approximately 15% of Earth's ice‐free continental surface and provide important water resources and ecosystem services to ∼1.2 billion people. Unlike silicates, carbonate minerals weather congruent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 278 publications
0
6
0
Order By: Relevance
“…However, this model does not adequately address critical geological factors, such as the hydrogeology and lithology of the catchment which can significantly impact the soil properties and hydrological processes (Covington et al., 2023; Virto et al., 2018). Most importantly, we do not account for effect of soil carbonates and pH of soil DOC cycling, although those have been found in empirical studies (see discussion in Rowley et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…However, this model does not adequately address critical geological factors, such as the hydrogeology and lithology of the catchment which can significantly impact the soil properties and hydrological processes (Covington et al., 2023; Virto et al., 2018). Most importantly, we do not account for effect of soil carbonates and pH of soil DOC cycling, although those have been found in empirical studies (see discussion in Rowley et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Dissolution may result from any potential acid source (e.g., equilibrium with atmospheric CO 2 , OC oxidation, nitrification, sulphide oxidation, etc. ; Covington et al, 2023; Martin, 2017) as surface water recharges the aquifer even following correction for mixing. For example, intruding surface waters are undersaturated with respect to calcite because of equilibration with atmospheric CO 2 (Brown et al, 2014; Gulley et al, 2011; Moore et al, 2010), which will contribute to the total observed dissolution and positive ΔCa 2+ diss/precip values.…”
Section: Discussionmentioning
confidence: 99%
“…Dissolution may result from any potential acid source (e.g., equilibrium with atmospheric CO 2 , OC oxidation, nitrification, sulphide oxidation, etc. ; Covington et al, 2023;Martin, 2017) as surface water recharges the aquifer even following correction for mixing.…”
Section: Possible Mechanisms Modifying Oc Oxidation and Limestone Dis...mentioning
confidence: 99%
“…), and is a three-dimensional landscape with solutional weathered surfaces and subsurface drainage systems [1,2]. Karst regions cover nearly 15% of the lands surface globally and are extremely valuable natural sites hosting a wide variety of unique ecological resources [3,4]. Karst aquifers provide freshwater to approximately 25% of the world's population and support related agriculture, groundwater, and ecosystems [5,6].…”
Section: Introductionmentioning
confidence: 99%